Non-operative management for oral cavity carcinoma: Definitive radiation therapy as a potential alternative treatment approach. (January 2021) - Hosni, Ali; Chiu, Kevin; Huang, Shao Hui; Xu, Wei; Huang, Jingyue; Bayley, Andrew; Bratman, Scott V.; Cho, John; Giuliani, Meredith; Kim, John; O'Sullivan, Brian; Ringash, Jolie; et al.
Highlights: Definitive RT/CRT for OSCC achieved acceptable rate of locoregional control. Definitive RT is a reasonable alternative treatment strategy if surgery is not possible. cN2-3 is associated with poor distant control, DFS, and OS. Abstract: Purpose: To determine the outcomes of oral cavity squamous cell cancer (OSCC) patients treated with non-surgical approach i.e. definitive intensity-modulated radiation therapy (IMRT). Methods: All OSCC patients treated radically with IMRT (without primary surgery) between 2005–2014 were reviewed in a prospectively collected database. OSCC patients treated with definitive RT received concurrent chemotherapy except for early stage patients or those who declined or were unfit for chemotherapy. The 5-year local, and regional, distant control rates, disease-free, overall, and cancer-specific survival, and late toxicity were analyzed. Results: Among 1316 OSCC patients treated with curative-intent; 108 patients (8%) received non-operative management due to: medical inoperability ( n  = 14, 13%), surgical unresectability ( n  = 8, 7%), patient declined surgery ( n  = 15, 14%), attempted preservation of oral structure/function in view of required extensive surgery ( n  = 53, 49%) or extensive oropharyngeal involvement ( n  = 18, 17%). Sixty-eight (63%) were cT3-4, 38 (35%) were cN2-3, and 38 (35%) received concurrent chemotherapy. With a median follow-up of 52 months, the 5-year local, regional, distant control rate, disease-free, overall, and cancer-specific survival were 78%, 92%, 90%, 42%, 50%, and 76% respectively. Patients with cN2-3 had higher rate of 5-year distant metastasis (24% vs 3%, p  = 0.001), with detrimental impact on DFS ( p  = 0.03) and OS ( p  < 0.02) on multivariable analysis. Grade ≥ 3 late toxicity was reported in 9% of patients (most common: grade 3 osteoradionecrosis in 6%). Conclusions: Non-operative management of OSCC resulted in a meaningful rate of locoregional control, and could be an alternative curative approach when primary surgery would be declined, unsuitable or unacceptably delayed.